Nursing Staff’s Experiences of Learning Palliative Care through Simulation Coaching: Learning palliative care - Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2022)
ABSTRACT The need to develop palliative care has been recognised in both the public and private sector. This qualitative study is based on self-assessed learning needs of staff in private elderly care and nursing services. This is a sub-study of a large research and development project, carried out in private care and welfare industries in one region of Finland in the years 2017-2019. The study describes nursing staff’s experiences of simulation coaching in learning palliative care at their own workplaces in nursing homes. The participants, employees of two enterprises providing residential elderly care and nursing services (n= 20), wrote essays describing the competence they had developed through palliative care simulations. The essays were analysed using inductive content analysis. The participants found the simulations suitable for learning palliative care. The intervention had been particularly effective in the areas of ethical competence, emotional intelligence, situational awareness and counselling competence. Simulation-based coaching seems a promising method for learning palliative care in both initial and continuing education programmes. Despite the limited sample size, the knowledge produced can be used to develop palliative care training.